Textbook of physical diagnosis history and examination - Swartz, Mark H. (Elsevier/Saunders, 2014)
Derive the maximum diagnostic information from interviewing and examining patients with Textbook of physical diagnosis. Employing a compassionate, humanistic approach, Dr. Swartz explores how cultural differences can influence communication, diet, family relationships, and health practices and beliefs, and demonstrates that your interpersonal awareness is just as essential in physical diagnosis as your level of technical skill. This medical reference book features numerous high-quality color images, an easy-to-use design, and detailed descriptions of exam techniques, making it an essential guide for physicians, nurse practitioners, and physician assistants.